(untitled) (Eurasian Research Bulletin, 2023)
The development of the information society leads to a shift from a material civilization to an invisible civilization, which it would be correct to call an information civilization. Information civilization creates huge opportunities for society and the economy. Internet functions such as remote work, distance learning or tele-information have their own social and economic consequences